2009
DOI: 10.1002/cvde.200906789
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ruthenium Thin Films from an Amidinate Precursor

Abstract: Ruthenium thin films were deposited by atomic layer deposition from bis(N,N'-di-tert-butylacetamidinato)ruthenium(II) dicarbonyl and O 2 . Highly conductive, dense and pure thin films can be deposited when oxygen exposure O E approaches a certain, the film peels off due to the recombinative desorption of O 2 at the film/substrate interface. Analysis by an atomic probe microscope shows that the crystallites are nearly free of carbon impurity (<0.1 at.%), while a low level of carbon (<0.5at.%) is segregated near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…In this proposed reaction mechanism, one of the key steps is that the oxidation step by oxygen not only removes any remaining organic ligands, but also forms the surface oxygen that readily reacts with following Ru(Cp) 2 pulse, thus completing the AB cycle of an ALD reaction. It is worth mentioning that for one particular group of metal‐organic precursors, those based on amidinate complexes, Ru metal can be achieved by using either O 2 or NH 3 as a co‐reactant in the ALD 92, 93. The use of a non‐oxidative reactant is desired in, for example, interconnect technology where the substrate beneath the Ru metal is sensitive to an oxidative environment.…”
Section: Thermal Ald Metallization Processes With An Ab Sequencementioning
confidence: 99%
“…In this proposed reaction mechanism, one of the key steps is that the oxidation step by oxygen not only removes any remaining organic ligands, but also forms the surface oxygen that readily reacts with following Ru(Cp) 2 pulse, thus completing the AB cycle of an ALD reaction. It is worth mentioning that for one particular group of metal‐organic precursors, those based on amidinate complexes, Ru metal can be achieved by using either O 2 or NH 3 as a co‐reactant in the ALD 92, 93. The use of a non‐oxidative reactant is desired in, for example, interconnect technology where the substrate beneath the Ru metal is sensitive to an oxidative environment.…”
Section: Thermal Ald Metallization Processes With An Ab Sequencementioning
confidence: 99%
“…The root-mean-square ͑rms͒ roughness values of these ALD films, 5 and 9.6 nm for the thermal and plasma-assisted ALD films, respectively, are very high for ALD films compared to the surface roughness values reported so far. For thermal ALD of Ru, rms surface roughness values are typically within the range of 0.3-3.8 nm ͑for film thicknesses ranging from 5 to 80 nm͒, 18,31,32,40 while for plasma-assisted ALD films even values as low as 0.7 nm have been reported for 50 nm thick films. 24 The results from the TEM measurements on the TiNcovered membranes are shown in Fig.…”
Section: 2431mentioning
confidence: 99%
“…12 roughness values ͑1.7 nm for a 5 nm thin film͒ for Ru prepared from EMR and O 2 at high substrate temperatures ͑T ϳ 400°C͒, 31 and Park et al 33 reported a surface roughness of 1.4 nm for a film of only ϳ3.1 nm thickness prepared from CpRu͑CO͒ 2 Et and O 2 at 300°C. Using a ruthenium amidanate precursor and O 2 , Wang et al 32 found that the surface roughness and grain size increase with longer O 2 gas exposures ͑with a maximum roughness of ϳ2.5 nm for an ϳ30 nm thick film͒ with the grain size distribution becoming also non-uniform. Furthermore, Kwon et al 18 carried out an experiment in which smooth Ru films ͑3.82 nm roughness for 80 nm film thickness͒ prepared by ALD at 270°C were annealed at 600 and 750°C in O 2 .…”
Section: 2431mentioning
confidence: 99%
“…Properties of the amidinates can be varied by changing the alkyl groups in the two nitrogen atoms. In addition, ruthenium films have been grown from amidinate (56). Amidinates have been used in deposition of many oxides, including challenging rare earth oxides (53,54).…”
Section: Metal Complexesmentioning
confidence: 99%